2019
DOI: 10.1039/c8nr09557d
|View full text |Cite
|
Sign up to set email alerts
|

Exploring T-carbon for energy applications

Abstract: Seeking for next-generation energy sources that are economic, sustainable (renewable), clean (environmentfriendly), and abundant in earth is crucial when facing the challenges of energy crisis. There have been numerous studies exploring the possibility of carbon based materials to be utilized in future energy applications. In this paper, we introduce T-carbon, which is a theoretically predicted but recently experimentally synthesized carbon allotrope, as a promising material for next-generation energy applicat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…Presently, various carbonaceous allotropes (Fig. 22b) [159], such as amorphous carbon [155], carbon nanotubes, graphite [157], and graphene [158], have been successfully employed in inorganic PSCs, ( fig.17a). In this strategy, the derivative phase films were sandwiched between the ETL and carbon electrode layer as shown in the fig.17d.…”
Section: Cspbbr 3 -Based Pscsmentioning
confidence: 99%
“…Presently, various carbonaceous allotropes (Fig. 22b) [159], such as amorphous carbon [155], carbon nanotubes, graphite [157], and graphene [158], have been successfully employed in inorganic PSCs, ( fig.17a). In this strategy, the derivative phase films were sandwiched between the ETL and carbon electrode layer as shown in the fig.17d.…”
Section: Cspbbr 3 -Based Pscsmentioning
confidence: 99%
“…In recent years, people found many 2D materials from allotropes of carbon and from group V elements. Some of them have potential application in optoelectronic, nano electronic devices and hydrogen storage, because of their unique electronic and mechanical properties [4][5][6][7][8][9][10]. In 2018, Cao et al found the twisted bilayer graphene is able to be an insulator or superconductor [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…prepared by picosecond laser irradiation on carbon nanotubes 26 and plasma-enhanced chemical vapor deposition 27 . The potential applications of T-carbon in photocatalysis, 3 solar cells, adsorption, energy storage, supercapacitors, aerospace materials, electronic devices are widely concerned 28,29 . With a hollow structure, T-carbon is expected to be a promising material for Li storage.…”
Section: Introductionmentioning
confidence: 99%